2020
DOI: 10.3390/ijms21207617
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptor in Adipose Tissue: Possible Association with Obesity-Related Elevated Autophagy

Abstract: Autophagy is upregulated in adipose tissue (AT) from people with obesity. We showed that activation of the calcium-sensing receptor (CaSR) elevates proinflammatory cytokines through autophagy in preadipocytes. Our aim is to understand the role of CaSR on autophagy in AT from humans with obesity. We determined mRNA and protein levels of CaSR and markers of autophagy by qPCR and western blot in human visceral AT explants or isolated primary preadipocytes (60 donors: 72% female, 23–56% body fat). We also investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…CVDs linked to obesity are mostly due to adipose tissue dysfunction, its enlargement, and the release of inflammatory factors from the adipose tissue [ 82 ]. Enlarged adipose tissues also show higher expression levels of CaSR [ 83 ]. It has been observed that the activation of CaSR in human preadipocytes stimulates autophagy, which is an essential mechanism for cellular homeostasis, because when damaged organelles are not degraded by lysosomes this leads to cardiometabolic comorbidities especially in conditions of obesity [ 84 ].…”
Section: Pathological Role Of Casr In Inflammation and Cardiovascumentioning
confidence: 99%
“…CVDs linked to obesity are mostly due to adipose tissue dysfunction, its enlargement, and the release of inflammatory factors from the adipose tissue [ 82 ]. Enlarged adipose tissues also show higher expression levels of CaSR [ 83 ]. It has been observed that the activation of CaSR in human preadipocytes stimulates autophagy, which is an essential mechanism for cellular homeostasis, because when damaged organelles are not degraded by lysosomes this leads to cardiometabolic comorbidities especially in conditions of obesity [ 84 ].…”
Section: Pathological Role Of Casr In Inflammation and Cardiovascumentioning
confidence: 99%
“…Furthermore, medium conditioned by adipose tissue explants from obese subjects increased CaSR expression in adipocytes and this CaSR expression was positively associated with BMI from the donor 50 . In addition, there is a positive correlation between CaSR mRNA expression in human vAT and fat percentage 51 . Therefore, it is possible that a more extreme condition, like obesity, is needed to distinctively elucidate the role of CaSR on adipose tissue inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…CASR exerted complicated functions in prostate, breast and colorectal cancer by regulating calcium homeostasis and inflammation 28–30 . Previous studies have shown that CASR could regulate autophagy in mammalian cells and that activation or overexpression of CASR induced autophagy, whereas inhibition or knockdown of CASR suppressed autophagy, which might be the molecular mechanism by which CASR regulates cancer 31–33 . Therefore, we speculated that NPS‐2143, the selective CASR antagonist, also might exert anti‐glioma ability by suppressing autophagy.…”
Section: Discussionmentioning
confidence: 96%